66P Efficacy and safety of nintedanib + docetaxel in lung adenocarcinoma patients (pts) following treatment with immune checkpoint inhibitors (ICIs): Updated results of the ongoing non-interventional study (NIS) VARGADO (NCT02392455). (15th December 2019) - Grohe, C; Gleiber, W; Krüger, S; Mueller-Huesmann, H; Schulze, M; Atz, J; Kaiser, R
Abstract: Background: Nintedanib (Vargatef®) is an oral triple angiokinase inhibitor blocking VEGF receptor (VEGFR), PDGFR and FGFR kinase activity. It is approved in the EU and other countries in combination with docetaxel for treatment of locally advanced, metastatic or locally recurrent NSCLC of adenocarcinoma histology after 1st line chemotherapy. Data are still limited regarding efficacy and safety of nintedanib in adenocarcinoma pts who had been pre-treated with ICIs. Methods: This interim analysis included 40 pts with locally advanced, metastatic or locally recurrent lung adenocarcinoma who received nintedanib and docetaxel following pre-treatment with chemotherapy and ICIs within the ongoing NIS VARGADO (cohort B); it updates and extends data previously presented at ESMO 2019. Results: Median age was 61 years (range: 45 – 80), 23/40 pts (57.5%) were men, and 26/40 pts (65.0%) were ECOG PS0/1. 10/40 pts (25.0%) had brain metastases, and 30/40 pts (75.0%) were current or former smokers. 1st line chemotherapy treatments included pemetrexed (29/40 pts, 72.5%), cisplatin (22/40 pts, 55.0%), carboplatin (21/40 pts, 52.5%), bevacizumab (11/40 pts, 27.5%), vinorelbine (6/40 pts, 15.0%), paclitaxel (3/40 pts, 7.5%), and docetaxel (1/40 pts, 2.5%). 2nd line treatments included nivolumab (25/40 pts, 62.5%), pembrolizumab (9/40 pts, 22.5%), and atezolizumab (5/40 pts, 12.5%). Under nintedanib and docetaxel, 13/29 pts (44.8%) developed a partial response and 12/29 pts (41.4%) showed stable disease; DCR was 86.2% (25/29 pts). Median PFS was 7.2 months (95%CI 2.9 – 8.7). Treatment emergent adverse events (TEAEs) grade ≥3, serious TEAEs, and TEAEs leading to discontinuation were observed in 17/40 pts (42.5%), 19/40 pts (47.5%), and 12/40 pts (30.0%), respectively. Conclusion: This updated analysis continues to show the clinical benefit and manageable safety profile of nintedanib plus docetaxel in pts with advanced adenocarcinoma NSCLC following treatment with chemotherapy and ICIs. Clinical trial identification: NCT02392455. Legal entity responsible for the study: Boehringer Ingelheim Pharma GmbH & Co. KG. Funding: Boehringer Ingelheim Pharma GmbH & Co. KG. Disclosure: C. Grohe: Advisory / Consultancy: Boehringer Ingelheim. H. Mueller-Huesmann: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): BMS; Honoraria (self), Advisory / Consultancy: Janssen; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Ipsen; Honoraria (self): AstraZeneca. J. Atz: Full / Part-time employment: Boehringer Ingelheim. R. Kaiser: Full / Part-time employment: Boehringer Ingelheim.